A Developmental Systems Guide for Child and Adolescent Behavioral Health Practitioners - Snyder, Sean E. (Open textbook library., 2023)
A Developmental Systems Guide for Child and Adolescent Behavioral Health Practitioners provides clinicians with actionable evidence-based practices for the assessment, diagnosis, and treatment of child and adolescent mental and behavioral health. This approach combines developmental psychology and ecological systems in recognition of the fact that children’s developmental challenges, tasks, and capacities intersect with the risks and protective factors of their environment. Chapters feature detailed case studies and conclude with conversations with clinicians in which they share targeted recommendations for patient evaluation, treatment approaches, and family engagement and support.